Estudos sobre educação bilíngüe e escolarização em contextos de minorias lingüisticas no Brasil - CAVALCANTI,Marilda C. (1999)
This paper aims at presenting a state-of-the-art of a subarea in Applied Linguistics, i.e., bilingual education studies in Brazil or yet education in bilingual settings such as indigenous communities, immigrant, frontier and deaf communities. These settings usually have more than two languages in use as well as language varieties. The paper shows a sociolinguistic panorama of the country and of the studies about education in linguistic minority contexts and draws implications for teacher education and language diversity.